2019
DOI: 10.3847/1538-4357/ab1de1
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Histories of the LEGUS Spiral Galaxies. I. The Flocculent Spiral NGC 7793

Abstract: We present a detailed study of the flocculent spiral galaxy NGC 7793, part of the Sculptor group. By analyzing the resolved stellar populations of the galaxy, located at a distance of ∼ 3.7 Mpc, we infer for the first time its radial star formation history (SFH) from Hubble Space Telescope photometry, thanks to both archival and new data from the Legacy ExtraGalactic UV Survey. We determine an average star formation rate (SFR) for the galaxy portion covered by our F555W and F814W data of 0.23 ± 0.02 M /yr over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 73 publications
3
15
0
Order By: Relevance
“…NGC 4449 and NGC 3738 are found to have approximately constant SFHs in the last 200 Myr (Cignoni et al 2018(Cignoni et al , 2019Sacchi et al 2018). Sacchi et al (2019) also reported that the SFH of NGC 7793, which contributes 40% of our final sample (see Table 1), is not bursty and suggests inside-out star formation in this galaxy. Further discussion can be found in Appendix B, where we demonstrate that complex stellar populations are still needed to explain the observations of some of our sources.…”
Section: Pahsupporting
confidence: 54%
“…NGC 4449 and NGC 3738 are found to have approximately constant SFHs in the last 200 Myr (Cignoni et al 2018(Cignoni et al , 2019Sacchi et al 2018). Sacchi et al (2019) also reported that the SFH of NGC 7793, which contributes 40% of our final sample (see Table 1), is not bursty and suggests inside-out star formation in this galaxy. Further discussion can be found in Appendix B, where we demonstrate that complex stellar populations are still needed to explain the observations of some of our sources.…”
Section: Pahsupporting
confidence: 54%
“…It is part of the Sculptor group, and is one of the closest galaxies in the LEGUS sample. It is characterized by diffuse, broken spiral arms with no bar, a very faint central bulge, and a relatively low star formation rate Sacchi et al (2019). study the star formation history of this galaxy using LEGUS data, whileGrasha et al (2017a,b) study the spatial and temporal TPCF of its star clusters.…”
mentioning
confidence: 99%
“…The photometry in Carignan (1985) as well as the measurements in Figure A28 show little to no color gradient across the galaxy. The SED-derived radial SFH of NGC 7793 (Figure A29) shows how NGC 7793 has a roughly constant SFH over its lifetime with the exception of the small bulge region, as mentioned in Section 5.1 and in Sacchi et al (2019). The similar results among all annuli included in the radial analysis suggests that the continuous SFH was experienced across the galaxy, and not limited to either the inner or outer regions.…”
Section: A11 Ngc 7793mentioning
confidence: 55%
“…Another galaxy from our sample that has had its CMD-derived SFH computed was NGC 7793 in Radburn- Smith et al (2012) and Sacchi et al (2019). Both of their results suggest that about 80% of the galaxy's stars were formed within the last 8 Gyr and 40% within the last 4 Gyr.…”
Section: Comparing To Resolved Stellar Populationsmentioning
confidence: 85%